Osteogenic differentiation of miniature pig mesenchymal stem cells in 2D and 3D environment - Juhásová, Jana; Juhás, Štefan; Klíma, Jiří; Strnádel, Ján; Holubová, Monika; Motlík, Jan (Physiological research, 2011)
Mesenchymal stem cells (MSCs) have been repeatedly shown to be able to repair bone defects. The aim of this study was to characterize the osteogenic differentiation of miniature pig MSCs and markers of this differentiation in vitro. Flow-cytometrically characterized MSCs were seeded on cultivation plastic (collagen I and vitronectin coated/uncoated) or plasma clot (PC)/plasma-alginate clot (PAC) scaffolds and differentiated in osteogenic medium. During three weeks of differentiation, the formation of nodules and deposition of calcium were visualized by Alizarin Red Staining. In addition, the production of alkaline phosphatase (ALP) activity was quantitatively detected by fluorescence. The expression of osteopontin, osteonectin and osteocalcin were assayed by immunohistochemistry and Western Blot analysis. We revealed a decrease of osteopontin expression in 2D and 3D environment during differentiation. The weak initial osteonectin signal, culminating on 7(th) or 14(th) day of differentiation, depends on collagen I and vitronectin coating in 2D system. The highest activity of ALP was detected on 21(th) day of osteogenic differentiation. The PC scaffolds provided better conditions for osteogenic differentiation of MSCs than PAC scaffolds in vitro. We also observed expected effects of collagen I and vitronectin on the acceleration of osteogenic differentiation of miniature pig MSC. Our results indicate similar ability of miniature pig MSCs osteogenic differentiation in 2D and 3D environment, but the expression of osteogenic markers in scaffolds and ECM coated monolayers started earlier than in the monolayers without ECM.
Keywords: buněčná diferenciace; Coloring Agents; Anthraquinones; osteokalcin; Sus scrofa; Extracellular Matrix; Tissue Scaffolds; extracelulární matrix; zvířata; Immunohistochemistry; imunohistochemie; Osteonectin; osteonektin; osteopontin; tkáňové podpůrné struktury; anthrachinony; mezenchymální kmenové buňky; Osteopontin; Cell Differentiation; barvicí látky; Animals; Mesenchymal Stem Cells; Osteocalcin